THE LANGUAGE FUNCTIONS USED BY TEACHERS OF CONTENT SUBJECTS USING ENGLISH AS THE MEDIUM OF INSTRUCTION (The Case of Mathematics and Science Teachers in Semesta Bilingual Senior High School) (Universitas Negeri Semarang, 2013)
This study aimed to describe the social and academic language functions of English employed in teaching content subjects and to explain the problems faced by the teachers when they taught content subjects using English. The data were obtained through classroom observation by recording the teaching and learning process with four different content teachers. The descriptive qualitative approach was usedto analyze the results of the study. The findings showed that 3 out of 4 content teachers had employed all kinds of social language functions. It indicated that they had a good ability to manage the classroom. In dealing with the academic language functions, it was found that all of the teachers had not used all kinds of academic language functions yet. It indicated that the teachers gave input more to the students by informing as mostly used. The result of this study revealed that the problems faced by teachers in using English were related to grammar,vocabulary, and pronunciation.Â Employing social and academic language functions are crucial for teachers. Social language functions maintain the social relationship among the teacher-students especially in managing the classroom. Meanwhile, the academic language functions give deeper knowledge and skills related to the content material.